Staging Ghana: Artistry and Nationalism in State Dance Ensembles. Paul Schauert. 2015. Bloomington and Indianapolis: Indiana University Press, 29 online media examples at Ethnomusicology Multimedia Series, 15 figures, bibliography, index, 343 pp. - Amoros, Luis Gimenez (International Library of African Music, 2017)
pages: 165-170
Keywords: Nationalism; African Music; Ghana; Artistry; Dance Ensembles